Assessment and analysis of innovative activities of high-tech industries in the digital economy based on the cluster approach (Nexo Revista Científica, 2021)
The purpose of the study is to analyze the level of digitalization of the economies of various countries of the world by dividing them into groups according to the level of digitalization of the economy through cluster analysis methods using a model for the development of high-tech industries. The following analysis methods were used during the analysis: a comparative approach in the analysis of approaches to the concept of "digital economy" by Russian and foreign authors, statistical analysis of indicators of the development of the digital economy of Russia and the countries of the world, cluster analysis in dividing the countries of the world into separate groups according to the level of development of the digital economy, morphological analysis and synthesis in the formation of the optimal structure of high-tech industries to increase the level of digitalization of the Russian economy, tabular and graphical methods to illustrate the results obtained. The result of the study is the formation of clusters of countries in the world according to the level of development of the digital economy and the application of a model for the development of high-tech industries in the country to increase the level of digitalization.